2015
DOI: 10.1038/nmat4206
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic fracture during epithelial stretching

Abstract: The origin of fracture in epithelial cell sheets subject to stretch is commonly attributed to excess tension in the cells’ cytoskeleton, in the plasma membrane, or in cell-cell contacts. Here we demonstrate that for a variety of synthetic and physiological hydrogel substrates the formation of epithelial cracks is caused by tissue stretching independently of epithelial tension. We show that the origin of the cracks is hydraulic; they result from a transient pressure build-up in the substrate during stretch and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(133 citation statements)
references
References 56 publications
6
126
1
Order By: Relevance
“…Furthermore, severing of actin filaments by cofilin after cessation of straining 13) implies that relaxation can be brought about even after single stretching. Consistently, both cell-generated traction force and intercellular tension have recently been reported to decrease after a single bout of cell stretching when compared with pre-stretching 14) . Considering that physiological mechanical stresses are mostly cyclic or transient, straining and relaxing mechanical stresses listed in Figure-4 are likely to be mixture or combined in vivo, excluding substrate (or matrix) stiffness.…”
Section: Straining and Relaxing (Mixed Or Combined) Mechanical Stresssupporting
confidence: 59%
See 1 more Smart Citation
“…Furthermore, severing of actin filaments by cofilin after cessation of straining 13) implies that relaxation can be brought about even after single stretching. Consistently, both cell-generated traction force and intercellular tension have recently been reported to decrease after a single bout of cell stretching when compared with pre-stretching 14) . Considering that physiological mechanical stresses are mostly cyclic or transient, straining and relaxing mechanical stresses listed in Figure-4 are likely to be mixture or combined in vivo, excluding substrate (or matrix) stiffness.…”
Section: Straining and Relaxing (Mixed Or Combined) Mechanical Stresssupporting
confidence: 59%
“…This may not just result from loosening of the tissues caused by plastic deformation (elongation). Post-stretching or -straining relaxation has been shown at cellular and molecular levels 13) 14) , suggesting that we can relax cells by applying straining mechanical stress in a regulated manner (mode, magnitude, location, duration, and frequency). Shear stress, which is a mixture of straining and relaxing, can also be utilized to relax cells.…”
Section: Beneficial and Detrimental Mechanical Stresses In Light Of Hmentioning
confidence: 99%
“…It is noteworthy that although it is shear stress force that plays a key role in altering micromechanical properties of KIF networks in AECs, as described before, a number of studies (5,7,30,31,39) have indicated that pressure gradients are more highly correlated with cellular mechanical damage, such as fracture or denudation of epithelial monolayers. With the consideration that a cell is a fluid sponge (cytosol and cytoskeleton), covered by a layer of an impermeable barrier [the plasma membrane (PM)], Oeckler et al (39) invoked the theory of poroelasticity to explain the dynamics of observational PM wounding.…”
Section: Discussionmentioning
confidence: 79%
“…8 and 9 that pressure gradients are increased with increasing dimensionless velocity Ca or viscosity . A number of recent studies (7,31,39) have demonstrated that the pressure gradient is the primary determinant of cell damage in the airway reopening. The experimental data from Kay et al (31) indicated that significant cell-membrane damage occurred when the fore-aft pressure changes across a cell (⌬P cell ) were ϳ300 dyn/cm 2 , which was reduced when ⌬P cell was ϳ120 dyn/cm 2 , and little membrane disruption was observed for ⌬P cell ϳ80 dyn/cm 2 .…”
Section: Alveolar Opening Anglesmentioning
confidence: 99%
“…Epithelium is another example of such tissues. Despite the intrinsic brittle behavior of the cell monolayer [9], this can display a high fracture toughness, as it has recently been shown experimentally [3]. In a previous work [11] we have demonstrated that this behavior is determined by the hydraulic coupling between the epithelial layer and the extracellular matrix, which can be regarded as a poroelastic, hydrogel-like material.…”
Section: Introductionmentioning
confidence: 78%